2022
DOI: 10.3390/toxins14040286
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Intracavernosal IncobotulinumtoxinA (Xeomin®) 100 U as an Add-on Therapy to Standard Pharmacological Treatment for Difficult-to-Treat Erectile Dysfunction: A Case Series

Abstract: Registered pharmacological treatments are insufficiently effective for erectile dysfunction (ED) in around 30% of affected men. Intracavernosal injection (ICI) of ona- and abobotulinumtoxinA can reduce ED in insufficient responders. We aimed to assess the safety and effectiveness of incobotulinumtoxinA ICI as an add-on therapy to phosphodiesterase-type 5 inhibitors (PDE5-Is) or prostaglandinE1 ICIs (PGE1 ICIs) to treat ED that did not respond sufficiently to this treatment alone. We retrospectively analyzed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…The results relating to safety are consistent with those of previous studies [ 11 , 12 , 13 , 14 , 15 , 16 ] and confirm that BTX/A ic is well tolerated and has a consistent safety profile over long-term, repeated treatment with no new safety signal. The only adverse effects were related to the intracavernosal injection procedure itself.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results relating to safety are consistent with those of previous studies [ 11 , 12 , 13 , 14 , 15 , 16 ] and confirm that BTX/A ic is well tolerated and has a consistent safety profile over long-term, repeated treatment with no new safety signal. The only adverse effects were related to the intracavernosal injection procedure itself.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, and conversely to previous findings regarding the effectiveness of the first BTX/A ic in men with ED and insufficient response to standard pharmacological treatment [ 16 ], ED severity on treatment prior to BTX/A ic did not seem to influence the response to repeated treatment after the first injection, as shown in Figure 2 . This might be explained by the fact that only the best responders requested further treatment among those with severe ED, whereas those with smaller responses did not request further injections.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…According to this study, the treatment effect lasted for more than three months with no reported collateral effects. The findings of this Phase I trial, have been confirmed and extended by other studies in patients with different botulinum neurotoxin A formulations and doses [41,[231][232][233] and are corroborated by animal studies [40,234], which support the promising role of intracavernous botulinum neurotoxin A in ED treatment. The mechanism by which botulinum neurotoxin A facilitates the relaxation of cavernous smooth muscles has not been clarified by the above studies.…”
Section: Botulinum Neurotoxin Asupporting
confidence: 79%
“…Starting just five years ago, a few studies have shown that botulinum neurotoxin A injected intracavernously was able to induce penile erection in patients with intractable ED and made them able to engage in sexual intercourse, and even to complete it, with the help of a PDe5 inhibitor. The effect was long-lasting (three-six months) with no collateral effect [40,41,[231][232][233][234]. These studies suggest that cavernous smooth muscles may be the target for this effect of botulinum neurotoxin A.…”
Section: Final Remarksmentioning
confidence: 73%